2021
DOI: 10.1186/s12963-020-00239-8
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth outcome capture and classification in population-based surveys: EN-INDEPTH study

Abstract: Background Household surveys remain important sources of stillbirth data, but omission and misclassification are common. Classifying adverse pregnancy outcomes as stillbirths requires accurate reporting of vital status at birth and gestational age or birthweight for every pregnancy. Further categorisation, e.g. by sex, or timing (intrapartum/antepartum) improves data to understand and prevent stillbirth. Methods We undertook a cross-sectional popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Misclassification in household surveys has been reported in several studies. 10 35–37 That this pattern appears largely confined to urban areas in our study warrants further investigation. We would expect better differentiation between these outcomes in an urban setting where higher quality services and more skilled personnel are available.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Misclassification in household surveys has been reported in several studies. 10 35–37 That this pattern appears largely confined to urban areas in our study warrants further investigation. We would expect better differentiation between these outcomes in an urban setting where higher quality services and more skilled personnel are available.…”
Section: Discussionmentioning
confidence: 64%
“…A second issue for research to understand in the association between neonatal mortality and urbanicity is the potential misclassification between stillbirths and neonatal deaths due to challenges with establishing whether there were signs of life after birth. 10 The combination of omission of stillbirths, potential misclassification of birth outcomes (neonatal deaths and stillbirths), misclassification or oversimplification of urbanicity and residual confounding may mask the true direction and strength of the association between urbanicity and neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In our sample, 385 mothers of stillborn babies out of 412 approached for interview consented to participate. The Every Newborn-INDEPTH multi-country study similarly investigated survey-reported data on stillbirth, including the feasibility of capturing information on timing of stillbirth [13,53].…”
Section: Discussionmentioning
confidence: 99%
“…The high degree of underreporting of stillbirths in the core urban area points to potential misclassification of stillbirths as neonatal deaths or general underreporting of stillbirths in these contexts. Misclassification in household surveys has been reported in several studies 13 47-49 and is related to factors such as how well vital status is assessed at birth and birth attendant’s ability to distinguish stillbirths from early neonatal deaths, socio-cultural perceptions of pregnancy loss that might affect disclosure, or intentional misclassification or underreporting to avoid blame or additional investigation depending on requirements in the context. That this pattern appears confined only to urban areas in our study warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the misclassification of urban areas, the outcome - neonatal mortality - may also be subject to misclassification with stillbirth due to challenges with establishing whether there were signs of life after birth. 13 To date, the DHS data does not include full data on stillbirths. Instead, pregnancy history is collected in the contraceptive calendar, and perinatal mortality (i.e., stillbirths and neonatal deaths) can be assessed.…”
Section: Introductionmentioning
confidence: 99%